INDUÇÃO DE RESISTÊNCIA A SECA EM Phaseolus vulgaris (L.) POR Bacillus E Trichoderma - Rati Minatto , Marcela; Eduardo Torres , Francisco; dos Santos Leite , Michele; Guilherme Romaike Catto, João; Burema Oliveira , Jacyeli; Pires Nepomuceno , Romeu (ANAIS DO ENIC, 2026)
-